The moderating role of corporate tax risks on the market valuation of tax savings: a new empirical evidence in the Indonesian context - Eko Suwardi; Mahfud Sholihin; Choirunnisa Arifa; Arfah Habib Saragih (Cogent Business & Management, 2024)
The primary aim of this study is to examine the moderating effect of corporate tax risks on the relationship between tax savings and firm value. A quantitative approach is utilized in this study. A total of 1813 firm-year observations from companies listed on the Indonesia Stock Exchange (IDX) from 2012 to 2017 comprise the sample. This study concludes that there is no moderating effect of tax risks on the relationship between tax savings and company value. This study emphasizes the importance of effective tax risk management for corporations in order to prevent investors from decreasing their evaluation of the organization's tax-saving endeavors. Further discussion will follow regarding the anticipated practical implications of this study for investors, tax authorities, and company management.
Keywords: 650; Tax savings; tax risks; firm value